SEMINAL FLUID MICROBIOTA AND MALE INFERTILITY: AN EMERGING FRONTIER - Gjatovska, Liljana Labacevska; Kostovski, Marko; Kovacheva-Trpkovska, Danica; Jovcevski, Radomir; Mihajlov, Kiril; Cekovska, Zaklina; Jankoska, Gordana; Grdanoska, Tatjana; Jurhar-Pavlova, Maja; Labachevski, Bojan (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Infertility is a multifaceted issue affecting millions globally, with male factors contributing to approximately 50% of cases. Traditionally, male infertility has been linked to genetic, hormonal, and environmental factors. However, emerging research highlights that disruptions or imbalances of the microbiota residing in the male reproductive tract, including the prostate, seminal vesicles, and urethra have significant implications for male reproductive health. Male urogenital system, particularly the urethra is home to a wide variety of microorganisms with rather high quantity. The composition of male genital microbiome can vary significantly between individuals and while the core microbiome is consised of a few dominant species a high variability is noted in minor species. It is predominantly composed of bacteria, with species from the genera Lactobacillus , Staphylococcus , Corynebacterium , and Propionibacterium being commonly found. Differentiating between pathogenic bacteria and the usual resident microflora is a difficulty in clinical practice, especially when it comes to male infertility. Furthermore, even though it is often benign, an imbalance in the commensal microbiota might encourage inflammation or foster an atmosphere that is favorable for pathogenic infections. Therefore, it is crucial to comprehend and maintain this equilibrium in order to create successful plans for the treatment and prevention of infertility. Traditional diagnostic approaches on male infertility focus on hormonal levels, sperm analysis, sperm culture and genetic factors, but unlike conventional culture methods which might find it difficult to distinguish between pathogenic and benign microorganisms because of genotypic and phenotypic overlaps and low pathogen presentation, developments in molecular methods for microbiota analysis, offer the possibility of more precise diagnosis and treatment of urogenital infections and imbalances. Modulating the genital microbiome could offer new treatment strategies for male infertility and related conditions. Keywords: microiota, infertility, male, reproductive.